1988
DOI: 10.1161/01.res.62.3.471
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence implicating a cytochrome P-450-mediated reaction in the contractile tension of the lamb ductus arteriosus.

Abstract: The authors have recently provided evidence implicating the cytochrome P-450 system in the generation of contractile tension of the ductus arteriosus. To confirm this possibility, carbon monoxide (CO/O2 ratio, 0.27) and cytochrome P-450 inhibitors [4-phenylimidazole; 14-isocyano,15-(methoxymethyleneoxy)-5Z,8Z,11 Z-eicosatrienoic acid; 9-hydroxyellipticine; alpha-naphthoflavone] were tested on the isolated ductus arteriosus from mature fetal lambs equilibrated at low (4-26 mm Hg) or high (229-694 mm Hg) O2 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…This suggests that mediators other than NO may stimulate sGC, increasing cGMP in the DA. Indeed, carbon monoxide has been shown to stimulate sGC and increase cGMP in various vascular beds, including the DA (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that mediators other than NO may stimulate sGC, increasing cGMP in the DA. Indeed, carbon monoxide has been shown to stimulate sGC and increase cGMP in various vascular beds, including the DA (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the vasorelaxation induced by CO and NO (17) including not only activation of sGC (11) but also stimulation of K ϩ channels (17,27) or inhibition of the cytochrome P450 monooxygenase (28,29). Hussain et al (30) have shown that ODQ completely abolished relaxation of rabbit aortic rings induced by CO, whereas only a partial attenuation of NO-induced relaxation was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In support of HO-1-mediated vasodilation, inhibition of HO activity increased blood pressure in spontaneously hypertensive rats (SHR) (Ndisang and Wang, 2002). The vasodilator effect of CO in various vessels may be due to a CO-mediated decrease in the cytochrome P450-dependent generation of vasoconstrictors (Coceani et al, 1988;Wang, 1998). Cytochrome P450 metabolizes arachidonic acid to the very potent vasoconstrictor, 20-HETE Schwartzman et al, 1996).…”
Section: Carbon Monoxide Production Ho-dependent Ho-independentmentioning
confidence: 99%